Micropump modeling: current status and challenges - Faris, Waleed Fekry; Asrar, Waqar; Omerbegovic, Adna (INSI Publications, 2012)
Micropumps are one product which was commercialized from Microsystem Industries. It has many applications and many potential as well, and due to this there is a growing interest in their modeling, simulation, and performance and this is going and in hand with research on their fabrication as well. In this paper, we are reviewing the basic aspects of modeling of micropump and their challenges. Basically, the microfluid behavior and the structural behavior in these devices. Also, we are exploring the fluid structural interaction.